Ivan Fedorovych Prokopenko is 85 years old! - Boychuk , Yu. (New Collegium, 2021)
The article is devoted to the description of the life path of the doctor of Pedagogy, professor, academician of the National Academy of Pedagogical Sciences of Ukraine Ivan Fedorovych Prokopenko, who has been working for 40 years as rector of H.S. Skovoroda Kharkiv National Pedagogical University — one of the leading higher pedagogical education institutions in Ukraine with high creative potential, where modern standards and technologies are being introduced, a new structure of organization and management of the educational process, the material and technical base is being strengthened, the volumes and quality of scientific and pedagogical personnel training are expanding. The main direction of the university’s activity during all the years of I.F.Prokopenko’s tenure as rector was the training of specialist teachers — nationally conscious citizens, patriots and real professionals. Academician I.F.Prokopenko has worked out and provided a new educational system for training a future teacher into the practice of higher pedagogical education, which is implemented through innovative pedagogical technologies aimed at developing the student’s personality, his creative potential. I.F. Prokopenko is an example of an intelligent and decent person, a talented and successful organizer of educational activities, an experienced and principled educator.